Effects of a Memory-Engaging Secondary Task in a Virtual Setting for Stimulating the Embodiment of an Artificial Upper Limb - Lucaroni, Andrea; Bottino, Andrea; Lamberti, Fabrizio; Mariani, Giulia; Marinelli, Andrea; Boccardo, Nicolo; Gruppioni, Emanuele; Michieli, Lorenzo De; Laffranchi, Matteo; Barresi, Giacinto (Conference proceedings (IEEE Workshop on Advanced Robotics and its Social Impacts.), 2024)
The embodiment (the sensation that an external object is part of one's body scheme) is one of the processes targeted by the research in bionic prosthetics as a potential strategy to increase the acceptance of artificial limbs. This study investigates how one of the components of the embodiment, the body ownership (the sensation of possessing the external object), may be affected by a secondary task (possibly competing for cognitive resources requested for the embodiment itself) in a virtual exergame for prosthetic training. In this preliminary study participants, without impairments, are asked to perform activities of pick-and-place in two conditions by using a digital model of the Hannes bionic hand: (i) one is cognitively challenging, requiring to memorize the sequence of objects to move before it disappears; (ii) the other is non-challenging for the subject's memory, with a constantly visible sequence. In both conditions, each subject is asked to catch objects according to the presented sequence. According to questionnaire data, we noticed how this procedure is feasible. Interestingly, the proprioceptive drift (the person is asked to indicate where they perceive their own real limb without looking at it) in a subsequent Rubber Hand Illusion session with the real bionic hand seems highlighting that the working memory-engaging secondary task can impair the embodiment process in terms of body ownership of the robotic hand. Probably, the memory task actually requires a type of cognitive resources that are necessary for the body ownership process itself during the multisensory stimulation. This allows for envisioning further investigations and novel design concepts for prosthetic training paradigms.